2004
DOI: 10.1177/107110070402501007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome (SF-36) of Patients with Displaced Calcaneal Fractures Compared to SF-36 Normative Data

Abstract: By comparing treatment for displaced intraarticular calcaneal fractures with treatment for orthopaedic problems or other disease processes, we concluded that intraarticular calcaneal fractures are serious life-changing events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“…Despite a smaller study population, the SF-36 scores in this study were comparable with data from a previous, well-powered study where data were obtained from 1 year to 2 years after operative treatment for displaced intra-articular calcaneal fractures. 35 Scores in this study as well as van Tetering and Buckley's study were found to be lower than normative Canadian values, 36 indicating the serious life altering impact of this injury. With regards to OAS scores, patients in both groups showed a nearly complete return to preoperative levels of function and pain (0/10) 2 years after treatment.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Despite a smaller study population, the SF-36 scores in this study were comparable with data from a previous, well-powered study where data were obtained from 1 year to 2 years after operative treatment for displaced intra-articular calcaneal fractures. 35 Scores in this study as well as van Tetering and Buckley's study were found to be lower than normative Canadian values, 36 indicating the serious life altering impact of this injury. With regards to OAS scores, patients in both groups showed a nearly complete return to preoperative levels of function and pain (0/10) 2 years after treatment.…”
Section: Discussioncontrasting
confidence: 69%
“…For analytical purposes, SF-36 scores were compared with previously collected Canadian scores after treatment of displaced intra-articular calcaneal fractures 35 as well as Canadian normative data for healthy individuals 36 Because of the difficult nature of patient follow-up in the trauma population, 2-year pain outcomes were completed verbally using Oral Analog Scale (OAS) scores 37 via clinical or phone interviews by a single, independent investigator. This scale has a maximum value of 10, with 0 signifying return to a preoperative pain-free state.…”
Section: Methodsmentioning
confidence: 99%
“…2 The SF-36 is a generic health status questionnaire that gives an indication of health-related quality of life. [20][21][22][23][24][25][26][27] The SF-36 consists of 36 items (questions) and provides scores on eight dimensions (subscales): physical functioning (PF), role limitations due to physical health problems (RP), bodily pain (BP), general health perceptions (GH), vitality (VT), social functioning (SF), role limitations due to emotional problems (RE) and general mental health (MH). These eight domains are combined into a physical component summary (PCS) and a mental component summary (MCS).…”
Section: Study Proceduresmentioning
confidence: 99%
“…Functional outcome after the treatment of a displaced intra-articular calcaneal fracture was compared with normative data, data on other orthopaedic conditions, and data on other medical conditions in a study of 312 patients by Van Tetering and Buckley 19 . Overall, the outcomes for patients with these fractures were not as good when compared with the population norms or with data on patients with other orthopaedic conditions, organ transplants, or myocardial infarction.…”
Section: Talar and Calcaneal Fracturesmentioning
confidence: 99%